Genomic characteristics of a novel emerging PRRSV branch in sublineage 8.7 in China - Li, Wansheng; Li, Chao; Guo, Zhenyang; Xu, Hu; Gong, Bangjun; Sun, Qi; Zhao, Jing; Xiang, Lirun; Leng, Chaoliang; Peng, Jinmei; Zhou, Guohui; Tang, Yandong; et al. (Frontiers in Microbiology, 2023)
Porcine reproductive and respiratory syndrome virus (PRRSV) has caused serious economic losses to the pig industry worldwide. During the continuous monitoring of PRRSV, a new PRRSV strain type with novel characteristics was first identified in three different regions of Shandong Province. These strains presented a novel deletion pattern (1+8+1) in the NSP2 region and belonged to a new branch in sublineage 8.7 based on the ORF5 gene phylogenetic tree. To further study the genomic characteristics of the new-branch PRRSV, we selected a sample from each of the three farms for whole-genome sequencing and sequence analysis. Based on the phylogenetic analysis of the whole genome, these strains formed a new independent branch in sublineage 8.7, which showed a close relationship with HP-PRRSV and intermediate PRRSV according to nucleotide and amino acid homology but displayed a completely different deletion pattern in NSP2. Recombinant analysis showed that these strains presented similar recombination patterns, all of which involved recombination with QYYZ in the ORF3 region. Furthermore, we found that the new-branch PRRSV retained highly consistent nucleotides at positions 117-120 (AGTA) of a quite conserved motif in the 3'-UTR; showed similar deletion patterns in the 5'-UTR, 3'-UTR and NSP2; retained characteristics consistent with intermediate PRRSV and exhibited a gradual evolution trend. The above results showed that the new-branch PRRSV strains may have the same origin and be similar to HP-PPRSV also evolved from intermediate PRRSV, but are distinct strains that evolved simultaneously with HP-PRRSV. They persist in some parts of China through rapid evolution, recombine with other strains and have the potential to become epidemic strains. The monitoring and biological characteristics of these strains should be further studied.